The influence of project-based learning strategies on the metacognitive skills, concept understanding and retention of senior high school students - Dominggus Rumahlatu; Kristin Sangur (Journal of Education and Learning (EduLearn), 2019)
Biology learning in the 21st century leads to the empowerment of metacognitive skills. Increased metacognitive skills can support concept understanding and maximize the students’ retention of concepts. This research aimed at investigating the effect of project-based learning strategy on metacognitive skills, concept understanding and retention of class X students of Senior High School 1 Kairatu, West Seram District, Maluku. This research is a quasi-experimental research using pre test-post test nonequivalent control group design. The samples of this research were all students of classX1 of Senior High School 1 Kairatu. The data obtained in this research were the learning results of metacognitive skills, concept understanding, and retention of the students. The data were analyzed by using analysis of covariance (ANCOVA). The research results showed that the implementation of project-based learning strategy had a significant effect on students’ metacognitive skills, concept understanding, and retention. Furthermore, the results of post hoc LSD test showed some differences in the notation between the project-based learning strategy and the conventional learning strategy. These results indicated that the learning stages of project-based learning strategy could empower the students’ metacognitive skills, concept understanding, and retention.